Influence of type of binder and sand on the characteristics of masonry mortars - Pereira, Manuel Fernando Paulo (2015)
This study deals with the characterization of masonry mortars produced with different binders and sands. Several properties of the mortars were determined, like consistence, compressive and flexural strengths, shrinkage and fracture energy. By varying the type of binder (Portland cement, hydrated lime and hydraulic lime) and the type of sand (natural or artificial), it was possible to draw some conclusions about the influence of the composition on mortars properties. The results showed that the use of Portland cement makes the achievement of high strength classes easier. This was due to the slower hardening of lime compared with cement. The results of fracture energy tests showed much higher values for artificial sand mortars when compared with natural sand ones. This is due to the higher roughness of artificial sand particles which provided better adhesion between sand and binder.